The investment behaviour of instutional investors in stock exchange markets : Evidence from İstanbul stock exchange - Okur, Mustafa (My University, 2008)
Behavioural Finance is a new approach in literature. Main idea is that, investors are not as rational as they are assumed to be. Therefore, financial markets could be better understood by using models which capture the effects of both rational and irrational investors. The critics of Behavioural Finance could be grouped into two main categories; limits of arbitrage and psychological factors. In this thesis, we concentrated on the psychological factors rather than limits of arbitrage. We empirically tested positive feedback trading and herding behaviour among institutional investors in Istanbul Stock Exchange. We used a weekly historical dataset. The high frequency of the data used differentiates the research from the other studies in the literature. We presented evidence of positive feedback trading and herding behaviour among institutional investors in certain stocks.

Davranışçı Finans, finans literatüründe yeni bir yaklaşımdır. Altında yatan temel düşünce, finans piyasalarındaki yatırımcıların aslında varsayıldığı kadar rasyonel olmadıklarıdır. Dolayısıyla finans piyasaları hem rasyonel hem de irrasyonel yatırımcıların etkilerini dikkate alan modeller yardımıyla daha iyi açıklanabilir. Davranışçı finansın yaptığı eleştiriler iki temel başlıkta toplanabilir; sınırlı arbitraj ve psikolojik faktörler. Bu çalışmada psikolojik faktörlerden ziyade sınırlı arbitraj üzerinde durulmuştur. İstanbul Menkul Kıymetler Borsa’sındaki kurumsal yatırımcıların pozitif tepki stratejileri ve sürü psikolojisi davranışları haftalık veri seti kullanılarak ampirik olarak test edilmiştir. Kullanılan yüksek frekansa sahip veri seti çalışmayı diğerlerinden ayırmaktadır. Uygulama sonuçları belli hisse senetlerinde kurumsal yatırımcılar arasında positif tepki stratejisin uygulandığı ve sürü psikolojisinin etkili olduğu gösterilmiştir.
Keywords: Davranışçı Finans; Yatırımlar